Interactions between erectile dysfunction, cardiovascular disease and cardiovascular drugs - Terentes-Printzios, Dimitrios; Ioakeimidis, Nikolaos; Rokkas, Konstantinos; Vlachopoulos, Charalambos (Nature reviews cardiology, 2022)
Sexual health has a fundamental role in overall health and well-being, and a healthy and dynamic sex life can make an important contribution to a good quality of life. Sexual dysfunction, and especially erectile dysfunction (ED) in men, is highly prevalent in patients with cardiovascular disease (CVD). CVD and ED have shared risk factors and pathophysiological links, such as endothelial dysfunction, inflammation and low plasma testosterone levels. ED has been shown to be an independent and early harbinger of future CVD events, providing an important window to initiate preventive measures. Therefore, screening and diagnosing ED is essential for the primary and secondary prevention of CVD because the assessment of ED offers an easy and low-cost prognostic tool that is an alternative to other investigational cardiovascular biomarkers. Moreover, ED is a major contributing factor to the discontinuation of, or poor adherence to, cardiovascular therapy. Cardiovascular drugs have divergent effects on erectile function, with diuretics and β-blockers having the worst profiles, and renin-angiotensin-aldosterone system inhibitors and nebivolol having the best profiles. Pharmacological treatment of ED has an equivocal effect on the risk of CVD, suggesting a complex interaction between ED and drugs for CVD. In this Review, we discuss how sexual function could be incorporated into the patient history taken by physicians treating individuals with CVD, not merely as part of the diagnostic work-up but as a means to pursue tangible and essential benefits in quality of life and cardiovascular outcomes.